Logical Specification of Operational Semantics - Mosses, Peter D. (BRICS Report Series, 1999)
Various logic-based frameworks have been proposed for specifying the operational semantics of programming languages and concurrent systems, including inference systems in the styles advocated by Plotkin and by Kahn, Horn logic, equational specifications, reduction systems for evaluation contexts, rewriting logic, and tile logic. We consider the relationship between these frameworks, and assess their respective merits and drawbacks - especially with regard to the modularity of specifications, which is a crucial feature for scaling up to practical applications. We also report on recent work towards the use of the Maude system (which provides an efficient implementation of rewriting logic) as a meta-tool for operational semantics.